The earliest directly dated rock paintings from southern Africa: new AMS radiocarbon dates. (4th April 2017) - Bonneau, Adelphine; Pearce, David; Mitchell, Peter; Staff, Richard; Arthur, Charles; Mallen, Lara; Brock, Fiona; Higham, Tom
Abstract: Abstract : Rock art worldwide has proved extremely difficult to date directly. Here, the first radiocarbon dates for rock paintings in Botswana and Lesotho are presented, along with additional dates for Later Stone Age rock art in South Africa. The samples selected for dating were identified as carbon-blacks from short-lived organic materials, meaning that the sampled pigments and the paintings that they were used to produce must be of similar age. The results reveal that southern African hunter-gatherers were creating paintings on rockshelter walls as long ago as 5723–4420 cal BP in south-eastern Botswana: the oldest such evidence yet found in southern Africa.